2014
DOI: 10.1155/2014/969420
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Peroneus Brevis Flap and Reverse Sural Artery Flap for Coverage of Lower One-Third Leg Defects

Abstract: Posttraumatic wounds and soft tissue defects in the distal third of the leg and ankle remain a challenge. Defects at this site will often require flap cover. Free flap is ideal for these defects and gives good results but with its own limitations. The reverse sural artery flap (RSAF) and distal peroneus brevis flap (DPBF) have gained popularity for lower third leg defects among surgeons. We did a retrospective study on 64 patients admitted between 2011 and 2013 with posttraumatic moderate size defects of lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
(27 reference statements)
1
5
0
Order By: Relevance
“…They recommended distally based peroneus brevis flap for small to medium defect for distal third of tibia, fibula, ankle and heel. Similar results were published by Thammannagowda et al 10 …”
Section: Discussionsupporting
confidence: 92%
“…They recommended distally based peroneus brevis flap for small to medium defect for distal third of tibia, fibula, ankle and heel. Similar results were published by Thammannagowda et al 10 …”
Section: Discussionsupporting
confidence: 92%
“…On comparing with these studies, it was found that flap tip loss, when used for medial malleolar defects, is well described, possibly due to the greater arc of rotation required and the resulting stretch [14,15].…”
Section: Table 2: Comparison Of Our Results With Similar Studiesmentioning
confidence: 99%
“…The prominent neurovascular structures included within the RSF are the sural nerve, superficial sural artery, and lesser saphenous vein. 21 The sural nerve is a cutaneous nerve that is typically formed from the merging of the medial sural cutaneous nerve and the lateral sural cutaneous nerve, which arises from the tibial nerve and common peroneal nerve, respectively. 22 The sural nerve can be found running between the 2 heads of the gastrocnemius muscle and descending into the deep fascia of the middle third of the leg.…”
Section: Anatomymentioning
confidence: 99%